KETAHANAN IDENTITAS BUDAYA MINANGKABAU DALAM DINAMIKA KEHIDUPAN PERANTAUAN - Selly Aprilia Santana; Rifda Sa’adatul Laila; Raisa Lastiana; Sifa Yustika (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
ABSTRACT Minangkabau culture is renowned for its unique matrilineal system and the tradition of migration (merantau) as an integral part of identity formation. This study aims to describe the resilience of Minangkabau cultural identity within the context of migration, focusing on the role of language, customary values, and informal education such as surau. The research employs a descriptive qualitative method using a narrative study approach based on the transcript of a personal interview with a Minangkabau migrant. The findings reveal that the use of the Minangkabau language and proverbs, such as “Dimano bumi dipijak, disitu langik dijunjuang” (wherever the land is stepped on, the sky above is upheld), serves as a moral compass in everyday interactions. Customary values, especially the role of the “mamak” (maternal uncle) in guiding and preserving family honor, remain crucial even when living far from the homeland. Surau is remembered as a vital space for nurturing religious and social character. However, modernization and the influence of foreign cultures pose significant challenges, particularly for younger generations who are increasingly distancing themselves from traditional values. Therefore, the revitalization of cultural values through family involvement and culturally-rooted education is essential to ensure the sustainability of Minangkabau cultural identity. This study provides insights for future programs on character education based on local wisdom, especially among Minangkabau migrants. ABSTRAK Budaya Minangkabau dikenal dengan sistem matrilineal yang unik dan tradisi merantau sebagai bagian penting dalam pembentukan jati diri. Penelitian ini bertujuan untuk mendeskripsikan ketahanan identitas budaya Minangkabau di tengah dinamika perantauan, dengan fokus pada peran bahasa, nilai adat, dan pendidikan informal seperti surau. Metode penelitian yang digunakan adalah deskriptif kualitatif dengan pendekatan studi naratif berdasarkan transkrip wawancara personal seorang perantau Minangkabau. Hasil penelitian menunjukkan bahwa penggunaan bahasa Minangkabau dan ungkapan adat seperti